WHO FEARS MATH MORE? GENDER INSIGHTS INTO MATHEMATICS ANXIETY - Rissa Isabella Taruli Marpaung; Tulus Joseph Herianto Marpaung; Rony Genevent Tonang Marpaung (Universitas Muhammadiyah Makassar, 2025)
This study aims to examine gender differences in mathematics anxiety among junior high school students at SMP Sangkara Medan in the 2024/2025 academic year. A quantitative comparative design was employed involving 35 students from grades 7 and 8. Data were collected using a validated mathematics anxiety questionnaire and analyzed using an independent samples t-test. The results revealed no statistically significant difference in mathematics anxiety between male and female students. These findings suggest that mathematics anxiety is a universal and context-dependent phenomenon, rather than an issue inherently associated with gender, highlighting the importance of inclusive instructional approaches.